Kaempferia galanga L. sebagai Anti-Inflamasi dan Analgetik - Reandy Ilham Andriyono (Jurnal Kesehatan, 2019)
Galangal (Kaempferia galanga l) is an herb that is often used in everyday life and widely used as a spice, food flavoring, and local tonic ingredients called ‘Jamu’. Galangal is a source of zinc, starch, ethyl ester, paraeumarin, borneaol, minerals, cinnamic acid, and other nutrients that are widely used in traditional medicine applications for a long time, especially in Southeast Asia. Besides that, it has medical functions, one of which is anti-inflammatory. Inflammation is a normal protective response to tissue injuries caused by physical trauma, damaging chemicals or microbiological substances. Inflammation can also be interpreted as the body's effort to activate or damage organisms that attack, eliminate irritants and regulate tissue repair. Signs of inflammation are redness, swelling, heat, and pain. Many chemical drugs are used to prevent inflammation, one of which is that modern drugs commonly used as anti-inflammatory drugs are NSAIDs (Non-Steroid Anti-inflammatory) Mechanism as an anti-inflammatory activity by elevating anti-inflammatory production IL-10, reducing pro-inflammatory IL-6 or TNF-a production, reducing the expression of iNOS and COX-2, inhibition of PG synthesis, Kaempferia galanga L also inhibits several inflammatory mediators TNF-α, IL-1β, and Nitric Oxide (NO) and angiogenesis.